A Facile Synthesis of Flower-like Iron Oxide Nanoparticles and Its Efficacy Measurements for Antibacterial, Cytotoxicity and Antioxidant Activity - Nazish Tabassum; Virendra Singh; Vivek K. Chaturvedi; Emanuel Vamanu; Mohan P. Singh (MDPI AG, 2023)
The objective of this study was to investigate the rhombohedral-structured, flower-like iron oxide (Fe2O3) nanoparticles that were produced using a cost-effective and environmentally friendly coprecipitation process. The structural and morphological characteristics of the synthesized Fe2O3 nanoparticles were analyzed using XRD, UV-Vis, FTIR, SEM, EDX, TEM, and HR-TEM techniques. Furthermore, the cytotoxic effects of Fe2O3 nanoparticles on MCF-7 and HEK-293 cells were evaluated using in vitro cell viability assays, while the antibacterial activity of the nanoparticles against Gram-positive and Gram-negative bacteria (Staphylococcus aureus, Escherichia coli, and Klebsiella pneumoniae) was also tested. The results of our study demonstrated the potential cytotoxic activity of Fe2O3 nanoparticles toward MCF-7 and HEK-293 cell lines. The antioxidant potential of Fe2O3 nanoparticles was evidenced by the 1,1-diphenyl-2-picrylhydrazine (DPPH) and nitric oxide (NO) free radical scavenging assays. In addition, we suggested that Fe2O3 nanoparticles could be used in various antibacterial applications to prevent the spread of different bacterial strains. Based on these findings, we concluded that Fe2O3 nanoparticles have great potential for use in pharmaceutical and biological applications. The effective biocatalytic activity of Fe2O3 nanoparticles recommends its use as one of the best drug treatments for future views against cancer cells, and it is, therefore, recommended for both in vitro and in vivo in the biomedical field.